Water Potentiality of Sustainable Management Challenges in the Oued Souf Region, south east Algeria - Miloudi, Abdelmonem1; Remini, Bouallem (جامعة الوادي - university of el oued, 2016)
Water is the most essential product of life and is a part of the essential constitution of living cells; it helps to carry out all the vital operations. Water is a cosmic element, in the same way as the sun and the earth. With the population growth in the Souf region, the needs of habitats and farmers increase for water. These needs have a negative consequence on the serene life of the people; the phenomenon of the upwelling of the free water table has taken a very alarming dimension during the last twentieth century. In our study, we focused our intention in the mechanism of the drawdown of the waters of the aquifer CT of state AL Oued (South East Algeria) and the consequences of irrational overexploitation of this aquifer on the environment of the region
Article
Keywords: the water, Souf region, CT, Overexploitation